Internationalizing Higher Education in Malaysia : Understanding, Practices and Challenges - Yean, Tham Siew (Book collections on Project MUSE., 2012)
This book examines the understanding, practices and challenges that Malaysia's higher education institutions face in their efforts to internationalize higher education at their respective institutions. This issue is of great importance to academics, policy-makers and students in institutions of higher learning in Malaysia, given the country's aspiration to become a hub for higher education. Malaysia is considered to be one of the success stories in the developing world in its efforts to internationalize its higher education. In the last decade or so, Malaysia has evolved into an emerging conte.